Efecto de la incorporación de harina de cáscara de plátano en la calidad de una salchicha Frankfurt tipo II - Párraga Román, Ignacio Antonio (2024)
The purpose of this research was to evaluate the effect of incorporating banana peel flour (Musa paradisiaca L. c.v. Dominico Harton) on the quality of a type II Frankfurt sausage. For this purpose, five treatments were proposed, four with different percentages of banana peel flour 2, 4, 6, 8%, and one treatment that represents the control with 4% wheat flour. The banana peel flour was subjected to physicochemical tests of humidity, protein, ash, acidity, fat, particle size, gluten, starch, along with microbiological tests, in accordance with the provisions of NTE INEN 616:2015, demonstrating the acceptability in all tests. Regarding type II Frankfurt sausages, a completely randomized experimental design (DCA) was applied, consisting of five treatments each with four repetitions. The results of the microbiological analyzes were acceptable in treatments T2, T3, T4, T5, in accordance with the provisions of NTE INEN 1338:2010. On the other hand, the bromatological quality was similar in the treatments compared to the control, and in the mechanical quality, T4 presented better elasticity and differs from the other variables. Finally, through sensory analysis, criteria were established that consumers prefer the color and flavor of treatments T2 and T3, demonstrating this, it is suggested that banana peel flour is a viable alternative to conventional flour in the production of Frankfurt sausages as it contributes to improving its quality.